Optimizing Teacher Performance Through School Management and Organizational Culture In Kepulauan Meranti Regency - Supiani, S; Kurniady, Dedy Achmad; Yuniarsih, Tjutju; Aedi, Nur (Jurnal Ilmu Sosial Mamangan, 2025)
This study aims to explore the impact of school management and organizational culture on the performance of middle school teachers in Kepulauan Meranti Regency. This research employs a quantitative approach, relying on data from a population of civil servant teachers in 41 middle schools in Kepulauan Meranti Regency. The total population sampled in this study consists of 143 teachers. Data were collected through direct distribution of questionnaires to respondents in a field study. Regression analysis methods were used to analyze the relationship between the independent variables (school management and organizational culture) and the dependent variable (teacher performance). The results of the data analysis show that simultaneously, school management and organizational culture have a significant impact on teacher performance. The calculated F value (8.945) is greater than the table F value (2.67), and the significance value of 0.000 is less than 0.05. Therefore, the null hypothesis is rejected, and the alternative hypothesis is accepted, indicating that these variables collectively have a significant impact on the performance of middle school teachers in Kepulauan Meranti Regency. This study is limited to the population of civil servant middle school teachers in Kepulauan Meranti Regency, so the results may not be generalizable to teachers in other regions or with different employment statuses. The findings of this study provide practical implications for school administrators and educational policymakers to enhance teacher performance through improvements in school management and organizational culture, as well as effective workload management. This research contributes to the literature on the impact of school management, organizational culture, and workload on teacher performance in remote areas, which has been understudied.